1996
DOI: 10.1007/bf02988836
|View full text |Cite
|
Sign up to set email alerts
|

Acute leukaemia following renal transplantation

Abstract: Four renal transplant patients on immunosuppressive therapy who presented with acute myeloid leukaemia are described. In two cases, azathioprine may have played an important role as a cofactor in leukaemogenesis. In a third case, the alkylating agent cyclophosphamide may have contributed. All patients were treated for leukaemia with full doses of cytotoxic chemotherapy and, in each case, a functioning renal allograft was preserved throughout the treatment despite attenuation of immunosuppressive therapy. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…There are sporadic case reports of AML/MDS in recipients of organ transplants (see, for example, Ferry et al 37 and Subar et al 38 ), and Huebner et al 39 have described 5 within a single institution. Our analysis of more than 170 000 patients provides unequivocal evidence that organ transplantation and long-term immunosuppression are associated with an increased risk for this disease.…”
Section: Discussionmentioning
confidence: 99%
“…There are sporadic case reports of AML/MDS in recipients of organ transplants (see, for example, Ferry et al 37 and Subar et al 38 ), and Huebner et al 39 have described 5 within a single institution. Our analysis of more than 170 000 patients provides unequivocal evidence that organ transplantation and long-term immunosuppression are associated with an increased risk for this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Acute leukemias and MDS occurring in recipients of solid organ transplants were either considered rare or thought to occur at rates similar to the general population [10][11][12][13][14][15]. However, recent studies have reported an increased risk of AML in patients who have undergone solid organ transplantation, which has largely been attributed to azathioprine toxicity [10,11,16,17]. The incidence and etiology of MDS post-solid organ transplantation are not well understood, although aza-thioprine induced DNA damage has also been implicated in the pathogenesis of these disorders [12,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have reported an increased risk of AML in patients who have undergone solid organ transplantation, which has largely been attributed to azathioprine toxicity [10,11,16,17]. The incidence and etiology of MDS post-solid organ transplantation are not well understood, although aza-thioprine induced DNA damage has also been implicated in the pathogenesis of these disorders [12,16,17]. Moreover, since chromosome 7 abnormalities are frequently observed in AML/MDS following treatment with azathioprine, mechanisms similar to alkylating therapy-associated MDS are thought to underlie MDS post-solid organ transplantation [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Several cases with AML post-renal transplantation have been published. 7,[9][10][11][12][13][14][15][16][17][18][19] One patient with AML out of a series of 124 cardiac allograft recipients has been reported. 20 AML as a complication of lung or liver transplantation has not been described yet.…”
Section: Introductionmentioning
confidence: 99%